Government Decentralization and International Government Performance - Rajeev K. Goel; Ummad Mazhar; Michael A. Nelson; Rati Ram (Center for Economic Studies and ifo Institute (CESifo), 2016)
Adding to the literature on the effects of government decentralization, this paper uses a large sample of individual responses from more than a hundred countries about public's perceptions of government's performance along various dimensions to study the relative influences of different types of decentralization, including fiscal decentralization, administrative decentralization, federalism, and aggregate decentralization. Our results show that fiscal and administrative decentralization are qualitatively alike in that greater decentralization in each case improves perceptions of the government performance. Federalist states' performance and overall decentralization are viewed somewhat differently. With regard to tax administration particularly, fiscal and administrative forms of government decentralization result in better outcomes than overall decentralization. Finally, service industries and large firms, ceteris paribus, perceived government performance differently.
Keywords: H11; H70; K20; K40; 330; fiscal decentralization; administrative decentralization; federalism; aggregate decentralization; government; tax administration; business permits